If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 81 + -1ysquared = 0 Solving 81 + -1adeqrsuy = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-81' to each side of the equation. 81 + -81 + -1adeqrsuy = 0 + -81 Combine like terms: 81 + -81 = 0 0 + -1adeqrsuy = 0 + -81 -1adeqrsuy = 0 + -81 Combine like terms: 0 + -81 = -81 -1adeqrsuy = -81 Divide each side by '-1deqrsuy'. a = 81d-1e-1q-1r-1s-1u-1y-1 Simplifying a = 81d-1e-1q-1r-1s-1u-1y-1
| 3x+48=156 | | (3x+1)=2 | | (x-5)squared=21 | | -180=-3x-3(7x+12) | | 4x-16y=4 | | 3yds=inches | | -10x-7=-11x+16 | | 3(u+9)=-4(3u-6)+6u | | x-146=70+10x | | 9x^3-15x^2+2=0 | | (cos(x)*cos(y)-cot(x))dx-(sen(x)*sen(y))dy=0 | | (cos(x)*cosy-cot(x))dx-(sen(x)*sen(y))dy=0 | | (5x)(2x+8y)= | | 3x^2+82x+418=0 | | 6x(30+6)=6 | | .11y+.09(y+8000)=2520 | | 11y+.09(y+8000)=2520 | | (5x)(10xy)= | | 0.5x+2=5x-43 | | 12h=9+84 | | b^2+6b-4=-2 | | 27x=9x-2 | | h(x)=4x^2+36 | | (cosx*cosy-cotx)dx-(senx*seny)dy=0 | | x^2-22x+437=0 | | -46+3x=80+12x | | (cosx*cosy-cotx)dx-(sinx*siny)dy=0 | | 11y=165 | | 3x^2+4x+14=0 | | 0.8+4.8=7.2 | | z-9.2=8.5 | | 6r-1+6r=119 |